Automated electrokinetic stretcher for manipulating nanomaterials - Soh, Beatrice W. (2023)
In this work, we present an automated platform for trapping and stretching individual micro- and nanoscale objects in solution using electrokinetic forces. The platform can trap objects at the stagnation point of a planar elongational electrokinetic field for long time scales, as demonstrated by the trapping of <100 nm polystyrene beads and DNA molecules for minutes, with a standard deviation in displacement from the trap center <1 μm. This capability enables the stretching of deformable nanoscale objects in a high-throughput fashion, as illustrated by the stretching of more than 400 DNA molecules within ∼4 hours. The flexibility of the electrokinetic stretcher opens up numerous possibilities for complex manipulation, with sequential stretching of a molecule at different voltages and multiple stretch-relaxation cycles of the same molecule as examples. The platform described provides an automated, high-throughput method to track and manipulate objects for real-time studies of micro- and nanoscale systems.